Multidisciplinary Nature of the Psycholinguistic Discourse Neuroeconomics - Тамара Ткач; Анатолій Ткач; Іван Рекун (Психолінгвістика)
Introduction. The article is devoted to the issues of multidisciplinary interaction in new scientific fields, which involve a wide variety of convergences, no matter how strange at first glance they may seem. One of these phenomena is the interaction of psycholinguistics and neuroeconomics.